Systematic Literature Review of Sustainable Tourism Village Development: Identification of Four Key Issues and Formulation of a Holistic-Resilient Circular Village (HRCV) Framework - Maria Anjelina Ngina Bali; Rochmad Bayu Utomo (Universitas Pancasakti Tegal, 2026)
Rural communities can become more economically independent through the development of tourism villages, which also helps increase Locally Generated Revenue (PAD). However, the full potential of tourism villages has not been fully realized due to several obstacles in its implementation. By reviewing and synthesizing previous research, this study hopes to identify these challenges and provide a more comprehensive framework to address them. This research uses a Systematic Literature Review (SLR) approach, utilizing the PRISMA flowchart and CASP tools for quality evaluation, on 20 international articles indexed in Scopus and Web of Science from 2019 to 2025. Three coding phases—open, axial, and selective—were used to analyze the data. Based on the data, four key issues commonly identified across countries are weak participatory governance, low economic resilience, conflicts in spatial planning, and limited human resource quality and digital literacy. Sustainable tourism villages can be built based on the revolutionary Holistic-Resilient Circular Village (HRCV) paradigm, which combines integrated spatial design, circular economy, participatory governance, and Penta Helix synergy.